Correlation of Humoral Immune Response in Southern Bluefin Tuna, T. maccoyii, with Infection Stage of the Blood Fluke, Cardicola forsteri - Kirchhoff, Nicole T. (Public Library of Science, 2012)

(untitled)
The blood fluke, Cardicola forsteri, is a prevalent infection in ranched southern bluefin tuna. This project aimed to define the timing and intensity of the various developmental stages of C. forsteri within southern bluefin tuna as well as to relate infection to host pathology and immune response. Archival samples from several cohorts of T. maccoyii sampled from 2008 to 2010 were used in this study. The prevalence and intensity of C. forsteri infection was described using heart flushes and histological examination. Humoral immune response, i.e. C. forsteri specific antibody, lysozyme activity, and alternative complement activity, was also described. Based on the validated and detailed C. forsteri infection timeline, relationships between infection events, physiological response, and diagnosis were proposed. Immune response developed concurrently with C. forsteri infection, with the majority of physiological response coinciding with commencing egg production. Further research is needed to confirm the origin of C. forsteri antigen which is responsible for immune response development and how T. maccoyii immune response works against infection. To aide this research, further diagnostic methods for confirmation of infection need to be developed.